Societal Impact of Test Automation: Reducing Human Error in Critical Systems - Sandeep Akinepalli, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the profound societal impact of test automation across critical sectors such as healthcare, finance, transportation, and energy. It examines how automated testing processes significantly reduce human error, enhance system reliability, and improve service quality. The article presents compelling evidence from various studies and reports, demonstrating substantial improvements in medical diagnostics, financial fraud detection, transportation safety, and energy distribution efficiency. Beyond error reduction, the article discusses broader societal benefits, including enhanced accuracy in data processing, faster emergency response times, improved service quality, and strategic resource allocation. The article underscores the crucial role of test automation in addressing the challenges posed by increasingly complex technological systems and its far-reaching implications for public safety, economic stability, and overall quality of life.
Keywords: Test Automation; Critical Systems; Error Reduction; Societal Impact; Technological Advancement